Does Short-Time Work Save Jobs? A Business Cycle Analysis - Almut Balleer; Britta Gehrke; Wolfgang Lechthaler; Christian Merkl (Center for Economic Studies and ifo Institute (CESifo), 2014)
In the Great Recession most OECD countries used short-time work (publicly subsidized working time reductions) to counteract a steep increase in unemployment. We show that short-time work can actually save jobs. However, there is an important distinction to be made: While the rule-based component of short-time work is a cost-efficient job saver, the discretionary component appears to be completely ineffective. In a case study for Germany, we use the rich data available to combine micro- and macroeconomic evidence with macroeconomic modeling in order to identify, quantify and interpret these two components of short-time work.
Keywords: E24; E32; E62; J08; J63; 330; short-time work; fiscal policy; business cycles; search-and-matching; SVAR